The DMD Locus Harbours Multiple Long Non-Coding RNAs Which Orchestrate and Control Transcription of Muscle Dystrophin mRNA Isoforms - Bovolenta, Matteo (Public Library of Science, 2012)
The 2.2 Mb long dystrophin (DMD) gene, the largest gene in the human genome, corresponds to roughly 0.1% of the entire human DNA sequence. Mutations in this gene cause Duchenne muscular dystrophy and other milder X-linked, recessive dystrophinopathies. Using a custom-made tiling array, specifically designed for the DMD locus, we identified a variety of novel long non-coding RNAs (lncRNAs), both sense and antisense oriented, whose expression profiles mirror that of DMD gene. Importantly, these transcripts are intronic in origin and specifically localized to the nucleus and are transcribed contextually with dystrophin isoforms or primed by MyoD-induced myogenic differentiation. Furthermore, their forced ectopic expression in both human muscle and neuronal cells causes a specific and negative regulation of endogenous dystrophin full length isoforms and significantly down-regulate the activity of a luciferase reporter construct carrying the minimal promoter regions of the muscle dystrophin isoform. Consistent with this apparently repressive role, we found that, in muscle samples of dystrophinopathic female carriers, lncRNAs expression levels inversely correlate with those of muscle full length DMD isoforms. Overall these findings unveil an unprecedented complexity of the transcriptional pattern of the DMD locus and reveal that DMD lncRNAs may contribute to the orchestration and homeostasis of the muscle dystrophin expression pattern by either selective targeting and down-modulating the dystrophin promoter transcriptional activity.